Clinical perspectives on the identification of neurodevelopmental conditions in children and changes in referral pathways: qualitative interviews. Issue 4 (13th April 2022) - Coughlan, Barry; Woolgar, Matt; Mann, Alissa; Duschinsky, Robbie
Abstract : Objective: Previous work has raised questions about the role of general practitioners (GPs) in the identification of neurodevelopmental conditions such as autism spectrum disorders (autism) and attention deficit hyperactivity disorders (ADHD). This study aimed to explore how GPs identify these conditions in practice and their perspectives on recent changes to local referral pathways that mean referrals to the neurodevelopmental team come through educational professionals and health visitors, rather than GPs. This study also aimed to explore Child and Adolescent Mental Health Services (CAMHS) specialist's perspectives on the role of GPs. Setting: GP practices, local neurodevelopmental services and specialist CAMHS services in the UK. Participants: semistructured interviews were conducted with GPs (n=8), specialists in local CAMHS (n=7), and professionals at national CAMHS services around the country (n=10). Interviews were conducted between January and May 2019. A framework approach informed by thematic analysis was used to analyse the data. Results: GPs drew on various forms of tacit and explicit information including behavioural markers, parental report, prior knowledge of the family, expert and lay resources. Opinions varied between GPs regarding changes to the referral pathway, with some accepting the changes and others describing it as a 'disaster'. CAMHS specialists tended to feel that GPs required more neurodevelopmental training and time to conduct consultations. Conclusion: This study adds to the literature showing that GPs use an array of information sources when making referral decisions for autism and ADHD. Further work is urgently required to evaluate the impact of reconfiguring neurodevelopmental referral pathways such that GPs have a diminished role in identification.